The Mediating Effect of Work Stress on the Relationship between Organizational Climate and Organizational Commitment - Vivi Gusnia Ningsih; Rini Sarianti (Universitas Negeri Padang, 2022)
This research aimed to identify the mediating effect of work stress on the relationship between organizational climate on organizational commitment The sample in this study was 73 nurses working on inpatient room of dr. Achmad Darwis Hospital in Suliki, Indonesia. Sampling techniques used total sampling. Data was collected through a questionnaire using Likert scale. Partial least square (PLS) was chosen as the structural equation model (SEM) to test the hypotheses. The results of this study indicate that (1) Organizational climate has a significant and positive effect on organizational commitment, (2) Organizational climate has a significant and negative effect on work stress, (3) Work stress has a significant and negative effect on organizational commitment, (4) Work stress significantly mediates the relationship between the organization's climate and the organizational commitment. Keywords: Organizational Climate, Organizational Commitment, Work Stress